2017
DOI: 10.1016/j.jagp.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obstructive Sleep Apnea with Episodic Memory and Cerebral Microvascular Pathology: A Preliminary Study

Abstract: Objectives Evaluate the impact of obstructive sleep apnea (OSA) on neurocognitive function and brain morphology in older adults with depression and cognitive impairment. Methods We prospectively screened OSA with the STOP-Bang questionnaire in the last 25 patients enrolled into the Donepezil Treatment of Cognitive Impairment and Depression (DOTCODE) trial. High and low probability of OSA were defined as a STOP-Bang score of ≥5 (h-OSA) and of <5 (l-OSA). Baseline MRI was used to evaluate brain morphology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…OSA is associated with AD pathophysiology, including amyloid burden and atherosclerosis ( Polsek et al, 2018 ; Lutsey et al, 2018 ; Sharma et al, 2018 ), and there is some evidence sleep-disordered breathing precipitates dementia ( Lutsey et al, 2018 ; Osorio et al, 2015 ; Emamian et al, 2016 ). Additionally, brain changes in OSA impact structures that are associated with AD-related cognitive decline ( Lutsey et al, 2016 ; Kerner et al, 2017 ), and the hippocampal changes shown here are another such finding. An intriguing possibility raised by the sex differences in OSA-related hippocampus volume changes is that the sleep disorder confers different risks for AD in females and males, a possibility raised over 30 years ago ( Smallwood et al, 1983 ).…”
Section: Discussionsupporting
confidence: 56%
“…OSA is associated with AD pathophysiology, including amyloid burden and atherosclerosis ( Polsek et al, 2018 ; Lutsey et al, 2018 ; Sharma et al, 2018 ), and there is some evidence sleep-disordered breathing precipitates dementia ( Lutsey et al, 2018 ; Osorio et al, 2015 ; Emamian et al, 2016 ). Additionally, brain changes in OSA impact structures that are associated with AD-related cognitive decline ( Lutsey et al, 2016 ; Kerner et al, 2017 ), and the hippocampal changes shown here are another such finding. An intriguing possibility raised by the sex differences in OSA-related hippocampus volume changes is that the sleep disorder confers different risks for AD in females and males, a possibility raised over 30 years ago ( Smallwood et al, 1983 ).…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, many studies have suggested that sustained attention deficits in OSAS patients are positively associated with motor vehicle accident risk [96,97]. The data provided by several studies revealed significant deficits in verbal but not visual memory [98][99][100]. A metaanalysis specifically focusing on memory problems in OSAS patients demonstrated significant impairments in immediate and delayed verbal and visuospatial memory and immediate visual recall [101].…”
Section: Brain Tissue Damage and Neurocognitive Dysfunction In Osasmentioning
confidence: 99%
“…OSA is highly prevalent in the middle-aged population and worsens with age. It is characterized by repetitive transient upper airway obstructions during sleep that result in either complete (apnea) or partial (hypopnea) pauses in breathing [99][100][101][102]. Periods of apnea are accompanied by periods of hypoxemia and by brief electroencephalographic and autonomic arousals that lead to a disruption of normal sleep architecture [101].…”
Section: Sleep Disruption In Age-related Comorbiditiesmentioning
confidence: 99%